Strategi Guru Dalam Mengembangkan Karakter Disiplin Pada Anak Usia Dini Di TK Pembina 1 Kota Bengkulu - Nawa Ulan; Ranny Fitria Imran; Rika Partika Sari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Teacher strategies in developing character discipline in early childhood in kindergarten Pembina 1 Bengkulu city Thesis of Early Childhood Education Teacher Education Study Program, Unive Bengkulu, 2024: 63 Pages. This study aims to analyze teacher strategies in instilling disciplined character in early childhood in TK Pembina 1 Bengkulu City. This study uses a qualitative approach with observation, interview, and documentation methods to collect data. The subjects of the study were teachers at TK Pembina 1, who were selected as key informants. The results of the study showed that teachers implemented various learning strategies to instill discipline, including direct and indirect learning strategies? After the direct learning strategy, the results were that children in TK Pembina 1 could understand the rules and develop good disciplined behavior, and the indirect learning strategy resulted in children in TK Pembina 1 being able to exemplify positive behavior from teachers.